Mesenchymal Stromal Cell-Derived Extracellular Vesicles Regulate the Mitochondrial Metabolism via Transfer of miRNAs - Loussouarn, Claire; Pers, Yves-Marie; Bony, Claire; Jorgensen, Christian; Noël, Danièle (Frontiers in Immunology, 2021)
Mesenchymal stem/stromal cells (MSCs) are the most commonly tested adult progenitor cells in regenerative medicine. They stimulate tissue repair primarily through the secretion of immune-regulatory and pro-regenerative factors. There is increasing evidence that most of these factors are carried on extracellular vesicles (EVs) that are released by MSCs, either spontaneously or after activation. Exosomes and microvesicles are the most investigated types of EVs that act through uptake by target cells and cargo release inside the cytoplasm or through interactions with receptors expressed on target cells to stimulate downstream intracellular pathways. They convey different types of molecules, including proteins, lipids and acid nucleics among which, miRNAs are the most widely studied. The cargo of EVs can be impacted by the culture or environmental conditions that MSCs encounter and by changes in the energy metabolism that regulate the functional properties of MSCs. On the other hand, MSC-derived EVs are also reported to impact the metabolism of target cells. In the present review, we discuss the role of MSC-EVs in the regulation of the energy metabolism and oxidative stress of target cells and tissues with a focus on the role of miRNAs.